Transformative CRISPR-Cas9 Technologies: A Review of Molecular Mechanisms, Precision Editing Techniques, and Clinical Progress in Sickle Cell Disease - Komal; Kaur, Prabhjot; Arora, Nidhi; Sawale, Jyotiram A.; Singh, Amandeep (Current Drug Metabolism, 2024)
Sickle cell disease (SCD) is a hereditary blood disorder resulting from the production of distorted hemoglobin molecules that cause red blood cells to adopt a sickle or crescent-like shape. This disease affects millions of people, particularly those of African, Mediterranean, Middle Eastern, or South Asian descent. In recent years, however, advancements in the CRISPR-Cas9 gene-editing systems have surged. CRISPR stands for clustered regularly interspaced short palindromic repeats, referring to a specific organization of short, partially repeated DNA sequences in prokaryotic genomes. The CRISPR-Cas9 technique is based on the type II CRISPR system of bacteria and involves the Cas9 nuclease, which is targeted to a particular genome section with the help of single-guide RNA. Initially used for random mutations and small sequence alterations, genome editing methods have advanced to achieve large-scale DNA segment manipulation. The BE and PE-type CRISPR-Cas9 genome editing variants provide new therapeutic options for genetic disorders, improving patients' prognosis. Curative gene editing using CRISPR-Cas9 technology to correct HBB gene mutations that cause SCD represents a revolutionary therapeutic development. These advances bring new hope to patients with previously untreatable diseases, potentially offering a future where genetic disorders can be addressed at their roots. A major objective of CRISPR technology is to enhance its precision and speed, both critical for effective gene editing. This review focuses on molecular mechanisms of CRISPR-Cas9 technology, CRISPR- Cas9-based approaches for HBB gene modification, clinical trials, patients with sickle cell disease, and advances in CRISPR technology for sickle cell disease.
Keywords: beta globin